"Plan de turismo comunitarios en el cantón colimes provincia del Guayas, año 2020" - Tapia León, Jenniffer Adriana (2020)
This research was carried out with the purpose of elaborating a community tourism plan that promotes entrepreneurship in rural populations of the Colimes canton, Guayas province, allowing the proper management of natural and cultural resources, promoting sustainable use, integration of the communities and the intervention of the municipality towards the tourism sector. A diagnosis of the general and tourist situation of the resources was made, identifying 115 emblematic saman trees, 17 rice plantations and 11 fruit trees, birds of different species, 1 archaeological site, 2 areas of guayacanes flowering, 2 herds, 2 stables, 22 howler monkeys, 1 bee farm (beekeeping), 1 historic house and 1 freshwater beach. On the other hand, a survey was conducted of 213 inhabitants, belonging to five communities, showing that 56% fully agree to participate in community tourism, 35% considered that they can offer food service and 31% lodging, but 25% indicated that the lack of a plan to guide and train them has impeded their development. In addition, was interviewed Mr. Nelson Burgos, providing relevant information about the work with the community and the reception that nature tourism has. Finally, a community tourism plan was developed structured as follows: mission, vision, 1 general objective and 3 specific ones, 5 programs, each with 3 strategies and 3 activities, responsible parties and the necessary budget with which it is sought to promote the spirit of undertaking and participating in community tourism, taking advantage of natural and cultural resources in a sustainable and sustainable way in constant care for the environment, managing to boost the economy of its inhabitants and promote the progress of tourism for the canton. Keywords: Tourism, communities, tourism resources, sustainable, tourism plan